Rumen microbiome response to sustained release mineral bolus supplement with low- and high-quality forages - Eberly, Jed O.; Wyffels, Samuel A.; Carlisle, Tanner J.; DelCurto, Timothy (Frontiers in Animal Science, 2023)
Limited forage quantity and quality are challenges faced in livestock production systems in semi-arid rangelands of the western United States, particularly when livestock face stressors such as cold weather or have increased nutritional requirements such as during pregnancy and lactation. To meet livestock nutrient requirements, producers frequently provide supplemental nutrition, however there is limited knowledge regarding the effects of these practices on the rumen microbiome in these environments. A study was conducted to evaluate changes in the rumen microbiome in response to high- and low-quality forage with sustained release mineral boluses. The study consisted of 16 ruminally-cannulated 2–3-year-old black angus cows fed high quality grass alfalfa hay or low-quality grass hay with a 90 or 180 day sustained release mineral bolus. Rumen samples were collected pre-feeding and 8 hours post feeding and bacterial 16S rRNA gene amplicons were sequenced from the rumen fluid. Alpha diversity as measured by Shannon’s diversity index decreased significantly over time (p<0.01) and averaged 5.6 pre-feeding and 5.4 post-feeding and was not significantly different between high- and low-quality forages or between mineral bolus types (p>0.05). Principal coordinates analysis (PCoA) of the Bray-Curtis dissimilarity matrix showed distinct grouping by feed quality and time but not by mineral bolus type. Bacteroidetes and Firmicutes were the dominant phyla in all treatments and significant increases (p<0.05) in the relative abundance of the family Lachnospiraceae and the genus Prevotella were observed in high quality forage diets. Rumen VFA and NH3-N concentrations were also strongly associated with the high-quality forage diet. Predictive functional profiling indicated that functions associated with methanogenesis were negatively correlated with feed quality. The results of this study suggest that mineral bolus type is unlikely to affect rumen bacterial community structure or function while forage quality can significantly alter community structure and predicted functions associated with methanogenesis and VFA production.